Mass spectra of alkaloids from cissampelos pareira l (1988)
The mass spectra of the tertiary bis-benzyl-isoquinoline alkaloids, warifteine and methyl-warifteine, extracted from the ethnobotanically important species, Cissampelos pareira L.. are discussed. Infonnation about the reltive positions of two hydroxyl and two methoxyl groups in warifteine and the presence of a p-xylyl moiety in both compounds in provided.